2012
DOI: 10.1136/archdischild-2012-302100
|View full text |Cite
|
Sign up to set email alerts
|

Drug use and upper gastrointestinal complications in children: a case-control study

Abstract: ObjectiveTo evaluate the risk of upper gastrointestinal complications (UGIC) associated with drug use in the paediatric population.MethodsThis study is part of a large Italian prospective multicentre study. The study population included children hospitalised for acute conditions through the emergency departments of eight clinical centres. Patients admitted for UGIC (defined as endoscopically confirmed gastroduodenal lesions or clinically defined haematemesis or melena) comprised the case series; children hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The most frequently reported therapeutic main group of drugs in previous European studies were antibiotics [18,34,35]. We instead found that vaccines (hexavalent, anti-pneumococcal, anti-meningococcus, trivalent measles/mumps/rubella) were those most commonly reported, in line with another observational survey [18,[36][37][38]. This finding may be explained by different prescription patterns in the various countries, the recent Italian governmental programs aimed at fostering the immunization coverage in the general population and the fact that in Italy the reporting of ADRs related to vaccines, at variance with other drugs, is compulsory [39].…”
Section: Number Of Adrssupporting
confidence: 86%
“…The most frequently reported therapeutic main group of drugs in previous European studies were antibiotics [18,34,35]. We instead found that vaccines (hexavalent, anti-pneumococcal, anti-meningococcus, trivalent measles/mumps/rubella) were those most commonly reported, in line with another observational survey [18,[36][37][38]. This finding may be explained by different prescription patterns in the various countries, the recent Italian governmental programs aimed at fostering the immunization coverage in the general population and the fact that in Italy the reporting of ADRs related to vaccines, at variance with other drugs, is compulsory [39].…”
Section: Number Of Adrssupporting
confidence: 86%
“…5,28,29 At an antipyretic dose, it may cause skin rash, respiratory and gastrointestinal effects including haematemesis. 27,30 Drotaverine and dicyclomine caused minor reactions. Antispasmodic drugs used in children for overactive bladder are usually oxybutynin and tolterodine.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1999 an active surveillance aimed at ascertaining the role of drugs and vaccines in the occurrence of specific acute conditions responsible for the hospitalization of paediatric patients has been conducted in Italy [13], [14], [15]. Non-infective muco-cutaneous diseases were among the conditions included in the surveillance and we focused on cases of SJS and TEN to contribute further information on the causal role of drugs and vaccines.…”
Section: Introductionmentioning
confidence: 99%